Will the green transition be inflationary? Expectations matter - Alessandro Ferrari; Valerio Nispi Landi (European Central Bank (ECB), 2022)
We analyse a gradual increase in the tax on emissions in a simple two-period New Key- nesian model with an AS-AD representation. We find that the increase in the tax today exerts inflationary pressures, but the expected further increase in the tax tomorrow depresses current demand, putting downward pressure on prices: we show that the second effect is larger. However, if households do not anticipate a future fall in income (because they are not rational or the government is not credible), the overall effect of the transition may be inflationary in the first period. We extend the analysis in a medium-scale DSGE model and we find again that the green transition is deflationary. Also in this larger model, by relaxing the rational expectations assumption, we show the transition may initially be inflationary.
Keywords: D84; E31; Q58; 330; Expectations; AS AD; Aggregate Prices; Climate Policy; Pollution Tax